2010
DOI: 10.1007/s11999-010-1245-4
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Tissue Biopsy in the Diagnosis of Periprosthetic Infection?

Abstract: Background Successful treatment of an infected joint arthroplasty depends on correctly identifying the responsible pathogens. The value of a preoperative biopsy remains controversial. Questions/purposes We (1) compared the sensitivity and specificity of both tests separately and in combination, and (2) asked whether the combination of tissue biopsy and aspiration would improve our diagnostic yield in the evaluation of periprosthetic joint infections. Patients and Methods We prospectively followed 120 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 40 publications
0
53
1
2
Order By: Relevance
“…To this end, numerous researchers have focused on improving existing methods for diagnosing infection (ie, preoperative and intraoperative cultures [2,3,16,27,46] and Gram stain [2,12,20,49], serum markers of inflammation [19,23,27], synovial white blood cell [WBC] count and polymorphonuclear [PMN] percentages [5,21,29,34,48], intraoperative frozen section [11,14,15,17,42] and preoperative tissue biopsy [32,36], and nuclear medicine…”
Section: Introductionmentioning
confidence: 99%
“…To this end, numerous researchers have focused on improving existing methods for diagnosing infection (ie, preoperative and intraoperative cultures [2,3,16,27,46] and Gram stain [2,12,20,49], serum markers of inflammation [19,23,27], synovial white blood cell [WBC] count and polymorphonuclear [PMN] percentages [5,21,29,34,48], intraoperative frozen section [11,14,15,17,42] and preoperative tissue biopsy [32,36], and nuclear medicine…”
Section: Introductionmentioning
confidence: 99%
“…In case of unexplained pain and/ or delayed wound healing, postoperative superficial infection, or persisting wound drainage, we obtained laboratory tests, radiographs, and a bone scan. When there was suspicion in the history for infection and C-reactive protein (CRP) or erythrocyte sedimentation rate (ESR) were increased or if there was a positive bone scan, a joint aspiration and biopsy were performed [25].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent bibliographic search performed by Meermans et al [17], spanning the period from 1988 to 2010, 29 different studies were found regarding joint aspiration sensitivity in PJI, for both hip and knee cases. A summary of these studies showed a joint aspiration sensitivity of 71% on average.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have used synovial biopsy, obtained by various techniques, in an attempt to improve outcomes, but with inconsistent results [17][18][19].…”
Section: Discussionmentioning
confidence: 99%